Komunikasi Interpersonal antara Ayah Nonbiologis dan Anak Perempuan Tiri dalam Membangun Kedekatan Emosional di Lingkungan Keluarga - Riza Insan Nabila; Rita Destiwati (Ranah Research : Journal of Multidisciplinary Research and Development, 2026)
This study aims to analyze the specific interpersonal communication barriers experienced by non-biological fathers in overcoming the emotional barriers of their stepdaughters. This study employs a qualitative approach using descriptive methods. The qualitative approach was chosen to examine social phenomena through a process of inductive reasoning, in which the researcher is directly involved in the subjects’ life context. The data in this study consist of the subjects’ verbal and non-verbal behaviors during the communication process. Indicators of interpersonal communication quality were systematically developed, covering the aspects of openness, empathy, supportiveness, positivity, and equality. The findings reveal that interpersonal communication in this relationship is effective when the father acts as a transparent and optimistic communication partner. Using warm messages and appreciation for the child’s learning process, negative stigma regarding the stepfather was significantly reduced